The moral obligation to have genetically related children - Pennings, Guido (Journal of medical ethics, 2025)
Donor conceived persons are likely to have a lower quality of life than persons who are genetically related to both parents. Empirical evidence is presented to corroborate this point. The evidence is subdivided into three sections: (1) negative experience of the donor conception itself, (2) negative effects of secrecy and openness and (3) negative effects of donor anonymity and donor identifiability. The principle of procreative beneficence requires parents to select the child with the best possible life. Given the difference in quality of life, intended parents should try to have a genetically related child. This finding is also a strong reason for society to invest public resources in the development of techniques that enable people to create genetically related children.